2019
DOI: 10.1139/cjz-2018-0145
|View full text |Cite
|
Sign up to set email alerts
|

Habitat type influences parasite load in Algerian Psammodromus (Psammodromus algirus) lizards

Abstract: Understanding how habitat type and deterioration may affect parasitism is important in assessing the effects of human-induced environmental change on host–parasite dynamics. In this study, we examined inter-population differences in parasite load in the Mediterranean lizard Psammodromus algirus (Linnaeus, 1758). We analyzed prevalence and intensity of infection by blood parasites and ectoparasites in two populations separated by a 400 m elevational gradient and with different habitat types that also differed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…This would also suggest the possibility of adaptive 'collection' of ectoparasites in environments where exposure to endoparasites is high-individuals with continuous immune response combating ectoparasites could be more resistant to endoparasitic infection. Interestingly, Carbayo et al (2018) found a similar relationship for ectoparasite-endoparasite infection to our finding on these two species, comparing two populations of P. algirus at different altitudes. In their study, they present that the lowland population was highly infected with endoparasites but not with ectoparasites, while for the highland population they found the opposite: low prevalence of endoparasites and high prevalence and infection intensity of ectoparasites.…”
Section: Discussionsupporting
confidence: 88%
“…This would also suggest the possibility of adaptive 'collection' of ectoparasites in environments where exposure to endoparasites is high-individuals with continuous immune response combating ectoparasites could be more resistant to endoparasitic infection. Interestingly, Carbayo et al (2018) found a similar relationship for ectoparasite-endoparasite infection to our finding on these two species, comparing two populations of P. algirus at different altitudes. In their study, they present that the lowland population was highly infected with endoparasites but not with ectoparasites, while for the highland population they found the opposite: low prevalence of endoparasites and high prevalence and infection intensity of ectoparasites.…”
Section: Discussionsupporting
confidence: 88%
“…In particular, the prevalence of ticks was higher in lizards from the high-elevation population (Carbayo, Mart ın & Civantos, 2019). Ticks are typically found grouped in hot spots just behind the armpit and the neck, where their action often exposed the skin below the scales (Salvador, Veiga & Civantos, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Amo, L opez & Mart ın, 2004;Knapp et al, 2019). Immune function is condition-dependent (Møller et al, 1998), and hosts in good condition may use more resources to resist infestation or to tolerate high intensities of parasitism (Budischak et al, 2018;S anchez et al, 2018;Carbayo, Mart ın & Civantos, 2019). If hosts use resources to fight parasites, hosts in poor condition could suffer impaired immune defence that would lead to greater probability of infection and heavier parasite loads, and ultimately higher mortality (Merino et al, 2000;Botzler & Brown, 2014).…”
Section: Introductionmentioning
confidence: 99%